Enhancement of dynamic load balancing using Particle Swarm Algorithm in Cloud Environment - Bansal, Ginni; Kaur, Amanpreet (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2016)
Dynamic load balancing with decentralized load balancer using PSO technique: Cloud consists of multiple resources and various clients request to the cloud for allocation of shared resources. Each request will be allotted to the virtual machines. In different situation different machines get different load. So to balance the load amongst different virtual machines decentralized load balancer is enhanced using particle swarm algorithm. The main objective is reducing the energy and increasing the throughput in comparison to centralized and simple decentralized load balancer using particle swarm optimization.